MENGUKUR KINERJA BANK PEMBIAYAAN RAKYAT SYARIAH - Ana Fitria; Ade Risma (FEB Universitas Syiah Kuala, 2022)
Banking financial performance is critical and must be assessed. This study aims to analyze the financial performance of an Islamic Rural Bank in Aceh, a province that adheres to sharia law in Indonesia. The RGEC method and sharia compliance indicators are used to see the financial performance of BPRS Taman Indah Darussalam during 2018-2020. By using a quantitative descriptive method, the results show that the Non Performing Financing (NPF) and Capital Adequacy Ratio (CAR) of this bank are at a very good level while the Return on Assets (ROA) is at a poor level and there is no Good Coprorate Governance (GCG